Rekreasi, Hiburan, Belajar: Studi Kegiatan Wisata Seni dan Budaya di Saung Angklung Udjo - Trianti Nugraheni; Agus Budiman; Dewi Rachmawati (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
Saung Angklung Udjo in West Java is one of the destinations for the arts and cultural tourism program founded by Mang Udjo Ngalagena. The concept of preservation, development and education of arts and culture is one of the program visions developed at Saung Angklung Ujdo. The purpose of this study was to obtain clear data and information related to the management system of the Saung Angklung Ujdo art and culture studio regarding how to plan, implement and program the marketing system implemented in Saung Angklung Ujdo, West Java. The method used in this research is descriptive method with a qualitative approach. The research data were obtained from structured interviews with the head of the studio management, field actors (performing artists) and several employees at Saung Angklung Udjo. Apart from the results of interviews, research data were obtained through the process of observation activities regarding the implementation of arts and cultural program activities at Saung Angklung Ujdo. The results showed that conceptually the arts and culture tourism program activities at Saung Angklung Udjo had a vision of activities in preservation, development and education. This is shown in the program objectives, activity materials, objectives and marketing strategies that have been developed to be more directed at organizing cultural and artistic tourism which has the principles of recreation, entertainment and learning.